Skeletal Muscle Wasting and Function Impairment in Intensive Care Patients With Severe COVID-19 - Andrade-Junior, Mario Chueire de; Salles, Isabel Chateaubriand Diniz de; de Brito, Christina May Moran; Pastore-Junior, Laerte; Righetti, Renato Fraga; Yamaguti, Wellington Pereira (Frontiers in Physiology, 2021)
BACKGROUND: Intensive care patients commonly develop muscle wasting and functional impairment. However, the role of severe COVID-19 in the magnitude of muscle wasting and functionality in the acute critical disease is unknown. OBJECTIVE: To perform a prospective characterization to evaluate the skeletal muscle mass and functional performance in intensive care patients with severe COVID-19. METHODS: Thirty-two critically ill patients (93.8% male; age: 64.1±12.6 years) with the diagnosis of the severe COVID-19 were prospectively recruited within 24 to 72 hours following intensive care unit (ICU) admission, from April 2020 to October 2020, at Hospital Sírio-Libanês in Brazil. Patients were recruited if older than 18 years old, diagnosis of severe COVID-19 confirmed by RT-PCR, ICU stay and absence of limb amputation. Muscle wasting was determined through an ultrasound measurement of the rectus femoris cross-sectional area, the thickness of the anterior compartment of the quadriceps muscle (rectus femoris and vastus intermedius), and echogenicity. The peripheral muscle strength was assessed with a handgrip test. The functionality parameter was determined through the ICU mobility scale (IMS) and the international classification of functionality, disability, and health (ICF). All evaluations were performed on days 1 and 10. RESULTS: There were significant reductions in the rectus femoris cross-section area (-30.1% [95% IC, -26.0% to -34.1%]; P < .05), thickness of the anterior compartment of the quadriceps muscle (-18.6% [95% IC, -14.6% to 22.5%]; P < .05) and handgrip strength (-22.3% [95% IC, 4.7% to 39.9%]; P < .05) from days 1 to 10. Patients showed increased mobility (0 [0-5] vs 4.5 [0-8]; P < .05), improvement in respiratory function (3 [3-3] vs 2 [1-3]; P < .05) and structure respiratory system (3 [3-3] vs 2 [1-3]; P < .05), but none of the patients returned to normal levels. CONCLUSIONS: In intensive care patients with severe COVID-19, muscle wasting and decreased muscle strength occurred early and rapidly during 10 days of ICU stay with improved mobility and respiratory functions, although they remained below normal levels. These findings may provide insights into skeletal muscle wasting and function in patients with severe COVID-19.